Three dimensional radiological assessment of the mediopalatine suture ossification and its correlation with biological age and orthodontic anomaly - Silvia Izabella Pop; Mariana Pacurar; Iulia Dumitrescu; Botond Fulop; Adriana-Rodica Muntean; Manuela Chibelean (Romanian Journal of Stomatology)
Introduction. Evaluating the ossification of the mediopalatine suture is crucial when considering Rapid Maxillary Expansion (RME) as a treatment option. Three-dimensional imaging, such as CBCT, enhances clinical practice in orthodontics by enabling personalized treatment based on individual patient characteristics. Objective. This study aimed to assess the morphology and degree of ossification/skeletal maturation of the mediopalatine suture using 3D imaging (CBCT). The secondary aim was to correlate the stages of suture maturation with patient age and skeletal anomalies. Material and method. CBCT images from 56 patients (aged 11 to 65 years) were analyzed. The mediopalatine suture maturation stages were determined according to Angelieri’s classification. Dental anomalies were diagnosed using comprehensive documentation. Statistical analysis was performed to correlate maturation stages with patient age and dental anomalies. Results. There was a weak and statistically non-significant negative correlation between patient age and suture maturation stage. Gender did not significantly influence the ossification of the mediopalatine suture. Conclusions. These findings suggest that the degree of ossification of the mediopalatine suture is independent of both the age of the patients and the presence of orthodontic anomalies.